2022
DOI: 10.1007/s00423-022-02662-x
|View full text |Cite
|
Sign up to set email alerts
|

How we do it—the use of peritoneal patches for reconstruction of vena cava inferior and portal vein in hepatopancreatobiliary surgery

Abstract: Purpose Extended resections in hepatopancreatobiliary (HPB) surgery frequently require vascular resection to obtain tumor clearance. The use of alloplastic grafts may increase postoperative morbidity due to septic or thrombotic complications. The use of suitable autologous venous interponates (internal jugular vein, great saphenous vein) is frequently associated with additional incisions. The aim of this study was to report on our experience with venous reconstruction using the introperative easi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…There are several vascular reconstruction techniques, and the optimal method is the one that provides the most significant opportunity for a safe R0/R1 resection of the tumor. Various types of grafts have been described for venous reconstruction; however, the decision for the optimal type depends on several factors, such as the vessel lumen, the type of vascular reconstruction (patch plastic or a tube substitute), the septic contamination of the operative field, the accessibility of the graft, and the surgeon's experience [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several vascular reconstruction techniques, and the optimal method is the one that provides the most significant opportunity for a safe R0/R1 resection of the tumor. Various types of grafts have been described for venous reconstruction; however, the decision for the optimal type depends on several factors, such as the vessel lumen, the type of vascular reconstruction (patch plastic or a tube substitute), the septic contamination of the operative field, the accessibility of the graft, and the surgeon's experience [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PPPs graft is readily available, operation time is not significantly prolonged, and there is no need for additional surgical procedures as in the case of harvesting another autologous vessel. In addition, there is no graft size limitation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…We adopted the Clavien–Dindo classification and Karnofsky performance scale to define the complications and functional status of patients in the postoperative period 6 . We used Radulova's criteria to define IVC patency 7 …”
Section: Methodsmentioning
confidence: 99%
“…1,2,47 Other authors have recommended lifelong anticoagulant treatment for reconstructions using synthetic materials or temporarily (up to 6 months) using autologous human materials. 7,32,37 However, a study in 2021 found no difference in thrombosis between patients who received anticoagulant or antiaggregant therapy and those who did not. 23 The ultimate goal was to find a completely nonthrombogenic material.…”
Section: Anticoagulation and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation